Carbon capture through solar-driven CO2 gasification of oil palm empty fruit bunch to produce syngas and biochar - Al-Muraisy, Saqr A.A.; Chuayboon, Srirat; Soares, Lais Americo; Buijnsters, J. G.; Ismail, Shahrul bin; Abanades, Stéphane; van Lier, Jules B.; Lindeboom, Ralph E.F. (My University, 2025)
Oil palm empty fruit bunch (OPEFB) is an abundant organic waste in Malaysia that is often disposed of through field burning. A previous study has shown that solar-driven steam gasification of OPEFB can produce hydrogen-rich syngas with an energy upgrade factor of 1.2 and a carbon conversion efficiency of 95.1 %. Beyond its potential as a biofuel, OPEFB can also act as a carbon sink, capturing photosynthetically stored carbon. This study explores the potential of amplifying OPEFB's negative carbon emissions through solar-driven gasification, using CO2 as the gasifying agent. In this work, a Central Composite Design (CCD) approach was employed to assess the influence of temperature (1100–1300 °C) and CO2/OPEFB molar ratio (1.6–3.0) on H2/CO molar ratio and energy upgrade factor, with a constant OPEFB flow rate of 1.8 g/min. The results demonstrated that at an energy upgrade factor of 1.4, 94.9 % of the total carbon was converted into syngas with a H2/CO molar ratio of 0.3. The maximum observed net carbon capture yield of 0.4 g C/g OPEFB was achieved at 1300 °C and a CO2/OPEFB molar ratio of 3.0. The remaining carbon (94.4–95.7 wt %) was converted into biochar with low heavy metal content, which has potential as a soil enhancer.
Keywords: Biochar; Biomass; Carbon capture; Concentrated solar power; Oil palm empty fruit bunch; Solar driven gasification